The Efficiency of MPPT in Mitigating the Effects of Partial Shading on Power Stability through the MPNO Method - Dionova, Brainvendra Widi; Devan Junesco Vresdian; Dian Nugraha; Ariep Janeul; Abir Oktaviani; M.N.Mohammed (Jurusan Teknik Elektro Universitas Andalas, 2025)
An electric vehicle charging station (EV charging station) is an infrastructure designed to charge electricity for electric vehicles. However, most EV charging stations still rely on fossil energy sources. Innovation is needed to overcome this problem. One of them is through the use of solar panels. Using solar panels on the CBMS turns it into a clean and environmentally friendly energy source. However, environmental factors such as weather significantly affect the energy conversion produced by solar panels. Panels that are covered by trees and tall buildings cause partial shading conditions. Partial shading conditions can result in a direct decrease in PV output power. To overcome this, output power optimization using a DC-DC converter is required. The MPPT boost converter system with a modified P&O method is designed to maximize the output power of solar panels when partial shading occurs. The test results show that the developed system can maximize the output power of solar panels in partial shading conditions with an average power increase of 8.13 and an efficiency of 91%. This method can reduce the negative impact of changes in light intensity, keep the system close to the maximum power point, and improve the efficiency of charging electric vehicles at SPKL during unstable weather conditions. However, the modified P&O method is less effective in maximizing the output power in standard solar panels. This research does not address the effectiveness of solar panels concerning temperature, humidity, and dust.